Risk of ischemic stroke associated with anti-rheumatic agents in patients with rheumatoid arthritis: A nationwide population-based case-control study - Soo Min Ahn; Seonok Kim; Ye-Jee Kim; Seokchan Hong; Chang-Keun Lee; Bin Yoo; Ji Seon Oh; Yong-Gil Kim (PLoS ONE, 2025)
Introduction Patients with rheumatoid arthritis (RA) face a significantly higher risk of major adverse cardiovascular events, including stroke, due to the pivotal role of inflammation in atherosclerosis and thrombosis. Various anti-rheumatic agents may influence stroke risk either by increasing or decreasing it, and this effect remains unclear. This study aimed to investigate the association between different anti-rheumatic agents and the risk of incident stroke in patients with RA using a nationwide claims database. Methods In this nested case-control study, the Korean Health Insurance Review and Assessment data of 35,133 patients newly diagnosed with seropositive RA from January 2011 to December 2020 were used. Incident ischemic stroke cases were identified and matched with randomly selected controls at a 1:4 ratio. The usage of anti-rheumatic agents was measured from the date of RA diagnosis to the index date and stratified in terms of exposure time and duration. The risk of stroke associated with each anti-rheumatic agent was estimated using conditional logistic regression and adjusted for comorbidities and concomitant drug use. Results Of the 35,133 patients, 1,386 (3.9%) cases were newly diagnosed with new-onset stroke. Thus, 1,384 stroke cases and 5,499 controls with newly diagnosed RA were included in the analysis. Current exposure to sulfasalazine (aOR: 0.79, 95% CI: 0.65–0.97) and hydroxychloroquine (aOR: 0.83, 95% CI: 0.72–0.96) was associated with a decreased risk of stroke, while current exposure to glucocorticoids (aOR: 1.71, 95% CI: 1.46–2.00) and tocilizumab (aOR: 3.47, 95% CI: 1.70–7.08) was related to an increased risk of stroke. Conclusion In this nationwide cohort study of patients with RA, treatment with sulfasalazine and hydroxychloroquine was associated with a decreased risk of stroke, while glucocorticoids and tocilizumab were linked to an increased risk of stroke. The association of tocilizumab with stroke should be cautiously interpreted due to the statistical limitations.